2006
DOI: 10.3748/wjg.v12.i2.280
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factors A and C in human pancreatic cancer

Abstract: VEGF-A and VEGF-C are commonly overexpressed in human pancreatic cancer and may contribute to tumor growth and lymph node metastasis. There is no relationship between the expression of VEGF-A and VEGF-C in pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 29 publications
2
45
1
2
Order By: Relevance
“…Taken together with the observation that EFEMP1 overexpression stimulates VEGF production in vivo, our findings are concordant with reports of the up-regulation of VEGF in pancreatic cancer (34)(35)(36). In contrast to our data that support a role of EFEMP1 in tumor progression in pancreatic adenocarcinoma, EFEMP1 expression was found down-regulated in lung cancer (37) and up-regulated in only 10% of different solid cancer entities (18).…”
Section: Discussioncontrasting
confidence: 53%
“…Taken together with the observation that EFEMP1 overexpression stimulates VEGF production in vivo, our findings are concordant with reports of the up-regulation of VEGF in pancreatic cancer (34)(35)(36). In contrast to our data that support a role of EFEMP1 in tumor progression in pancreatic adenocarcinoma, EFEMP1 expression was found down-regulated in lung cancer (37) and up-regulated in only 10% of different solid cancer entities (18).…”
Section: Discussioncontrasting
confidence: 53%
“…HIF helps to mediate responses to hypoxia (22). VEGF family members are commonly overexpressed in human pancreatic cancer and contribute to tumor growth and metastasis (23). We recently demonstrated that the metastatic potential of a human pancreatic cancer cell line HMET as compared with its nonmetastatic derivative LMET that was associated with increased expression of proangiogenic molecules, in particular, VEGF.…”
Section: Discussionmentioning
confidence: 98%
“…Immunohistochemical analysis of 50 pancreatic cancer tissue samples revealed the presence of VEGF-A immunoreactivity in 50% of the cancer tissue samples. The presence of VEGF-A in these cells was associated with larger tumor size and enhanced local spread but it was not associated with decreased patient survival [82]. VEGF-A significantly increased the motility of pancreas cancer cells playing an important role in inducing invasion and migration of pancreatic cancer cells [83].…”
Section: Pancreatic Cancermentioning
confidence: 92%
“…Moreover, in human pancreatic cancer and nude mice model, the expression of VEGF-C on lymphatic metastasis was higher than in primary tumor [89]. The presence of VEGF-C in the cancer cells was associated with increased lymph node metastasis, but it was not associated with decreased patient survival [86,82].…”
Section: Pancreatic Cancermentioning
confidence: 99%